OCCURRENCE OF Gymnodinium catenatum IN THE GULF OF THAILAND - Lirdwitayaprasit, Thaithaworn; Panuksubaksul, Darin; Takata, Yoshinobu; Sato, Shigeru; Kodama, Masaaki; Fukuyo, Yasuwo (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 2008)
A clonal culture of Gymnodinium catenatum was established from a plankton sample collected from Leamthan, Chonburi Province, in the Upper Gulf of Thailand. The culture was maintained at 28±1°C under light intensity of 70 [tmol photons m-2 s-1 with 12:12 L:D cycle. Cells were harvested at late exponential phase and extracted with 0.03 M acetic acid. The HPLC analysis on thus obtained extract revealed that toxins consist of N-sulfocarbamoyl toxins, Cl and C2, as major components. GTX1, GTX2, GTX3, GTX4 and dcSTX were also detected as minor components. The toxin profile of this clone is different from clones of G. catenatum found in Singapore which was dominated by the highly potent carbamate toxins, primarily GTX 1 and 4 with less amounts of GTX2, GTX3, neosaxitoxin, and saxitoxin. No N-sulfocarbamoyl, decarbaomyl, or deoxy-decarbamoyl toxins were detected.